Pentaceraster cumingi, new record of starfish (Asteroidea) for the Salvadoran Pacific - Ramos-Cáceres, María Fernanda (2022)
Having a biodiversity register is important for any region. In this paper, Pentaceraster cumingi is incorporated to El Salvador’s marine wealth. The objective was to document its presence in the Salvadoran Pacific. Based on photographic material, there is evidence of the existence of P. cumingi in a national reef since 2017. This species is vulnerable to be trapped in trawling nets. The densities and the ecological role it plays should be known.